Cornelia de Lange Syndrome: A Chronicle Review - Devadiga, Sumithra; V, Adarsh V; S, Bhagyashree; s, Savitha; Nayak, Ravikumar (Indian Journal of Pharmacy Practice)
Cornelia de Lange disorder (CdLS) may be an intrinsic condition stamped by a characteristic facial appearance, pre-birth and postnatal development lacking, eating challenges, psychomotor delay, behavioral clutters, and concomitant upper limit distortions. W. Brachmann archived the primary case of CdLS in 1916, taken after Cornelia de Lange, a Dutch pediatrician, in 1933, after whom the clutter was named. In any case, not each individual with CdLS has the normal phenotype and can show in an assortment of ways, extending from gentle to severe and with shifting degrees of confront and appendage inclusion. The essential instrument behind CdLS has been hypothesized to be dysregulated quality expression. Surgery may be used to treat diaphragmatic hernias, heart anomalies, and/or cleft sense of taste in a few children. Over-the-top hair development could be decreased with plastic surgery.
Keywords: Cornelia de Lange syndrome; Brachmann-de Lange syndrome; Craniofacial; Synophrys; Micrognathia